Banks’ distributional channel strategies, customer satisfaction and mediating role of trust - Mohammad, Haruna Isa; Bello, Kamarudeen Babatunde (Management and Entrepreneurship: Trends of Development, 2022)
The purpose of this paper is to investigate the impact of perception of banks’ distributional channel strategies (Human Teller, ATM-Banking, POS-banking, Mobile banking, internet banking) on customer satisfaction; and the mediating effects of trust in these relationships.  Cross-sectional (survey) data was obtained from a sample of 352 retail bank customers in north-east region of Nigeria, using pre-validated measures. The ADANCO 2.0.1 analytical package was employed in conducting the tests of hypotheses. Results indicate that only the human teller and internet banking channels influence customer satisfaction directly and indirectly through customer trust; while the influence of mobile banking channel on customer satisfaction is fully mediated by trust.  The research findings have further confirmed the irreplaceability of the human element in the delivery of banking services. Bank managers should emphasize continuous training and orientation of employees towards effective service delivery and relationship building. The findings also point to the need for bank managers to devise innovative means of improving the quality of services through self-service channels (ATM, POS and Mobile), and communicate such to customers; while putting measures in place to win the trust of customers for the channels and the entire services of the banks. This paper contributes to the body of knowledge on customer perceptions and response in a multi-channel banking environment, and the mediating role of trust, particularly from developing country perspective.  JEL Classification: L1, M31, M32.